The Central American species of Diplonevra Lioy (Diptera: Phoridae) - Corona, Emily M.; Brown, Brian V. (Zootaxa, 2005)
The species of Diplonevra Lioy of Central America are reviewed, with particular attention to the structure at the base of the posterior face of the hind femur. Six species are recognized, five of which are new to science: D. ereba, D. goliatha, D. hypermeka, D. truncatiseta, and D. gnoma. The sole described species, D. setigera (Malloch), is found to be a senior synonym of the North American D. gaudialis (Cockerell) and the Brazilian D. impressa (Borgmeier), both new synonyms.